Synthesis of Graphitic Mesoporous Carbon from Metal Impregnated Silica Template for Proton Exchange Membrane Fuel Cell Application. Issue 1 (21st January 2019) - Sultana, K. N.; Worku, D.; Hossain, M. T. Z.; Ilias, S.
Abstract: High surface area graphitic mesoporous carbons (M‐mGMC; M=Ni, Fe, Co or Ni‐Fe) were synthesized via catalytic graphitization using a hard template based synthesis method. In house prepared SBA‐15 silica material was impregnated with metal precursors to obtain M/SBA‐15, template for M‐mGMC synthesis. These materials were studied using different material characterization techniques, such as nitrogen adsorption desorption (BET), X‐ray diffraction (XRD) analysis, Raman spectroscopy, X‐ray photoelectron spectroscopy (XPS), Thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). Specific surface area ranging from 1, 227.9 m 2 g −1 to 1, 320.7 m 2 g −1 was observed for four M‐mGMCs. Raman spectroscopy, XPS and wide angle XRD suggested presence of graphitic structure in these materials along with disorders. Electrocatalytic performance of these materials along with conventional carbon black (Vulcan XC‐72) were evaluated in a single‐stack proton exchange membrane fuel cell (PEMFC). Pt/NiFe‐mGMC exhibited enhanced electrocatalytic activity compared to Pt/Ni‐mGMC, Pt/Fe‐mGMC and Pt/Co‐mGMC electrocatalysts. However, Pt/NiFe‐mGMC lacked adequate proton transport in membrane electrode assembly (MEA) compared to Pt/Vulcan XC‐72. This exploratory study showed that NiFe‐mGMC may find application as electrocatalyst support material in PEMFC.